Indoleamine 2,3-dioxygenase 1 in cancer immunotherapy: from small-molecule inhibition to PROTAC-mediated degradation - Li, Xiuyun; Meng, Hao; Wang, Hefeng; Zhang, Yujing; Yu, Wanpeng (Frontiers in Pharmacology, 2025)
Indoleamine 2,3-dioxygenase 1 (IDO1) has emerged as a critical immunometabolic regulator in cancer, orchestrating immunosuppression through its rate-limiting catabolism of tryptophan to kynurenine. This enzymatic activity establishes an immunosuppressive tumor microenvironment via two distinct pathways: GCN2-mediated T cell anergy resulting from tryptophan depletion, and AhR-dependent immune tolerance induced by accumulating kynurenine metabolites. The therapeutic landscape of IDO1 inhibition has progressed significantly from early heme-competitive inhibitors like epacadostat to next-generation proteolysis-targeting chimera (PROTAC) technology. While over 20 small-molecule IDO1 inhibitors have entered clinical trials for various cancers, their variable efficacy has underscored the need for improved target engagement strategies and better patient selection biomarkers. PROTACs represent a paradigm shift in IDO1 modulation, offering the unique advantage of complete target degradation rather than mere inhibition. This review systematically evaluates: (1) clinically investigated IDO1 inhibitors and their pharmacological profiles, and (2) the preclinical promise of IDO1-targeting PROTAC degraders. Through critical analysis of their mechanisms of action and therapeutic potential, we provide insights into optimizing IDO1-targeted strategies for cancer immunotherapy.